2021
DOI: 10.1063/5.0046922
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the solution-cathode glow-discharge and solution-anode glow discharge using a rotating magnetic field

Abstract: The effects of an external magnetic field on the solution-cathode glow-discharge (SCGD) and solution-anode glow-discharge (SAGD) are investigated. The SCGD is atmospheric-pressure glow discharge sustained between a metal pin and a liquid cathode electrode in the ambient atmosphere, and it is often used for trace elemental analysis by atomic emission spectroscopy. Here, the SCGD is modified to allow an external permanent magnetic field to be applied, either in a static orientation or as a rotating field, as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Third, the plasma can be operated with multiple arrangements of polarity, rather than the solution only serving as the cathode. (Ray and coworkers have very recently described a device which operates in SCGD and SAGD modes, with magnetic “boosting” for analysis; Hazel et al, 2021). Finally, a diversity of sample introduction modalities can be applied, inclusive of solids, liquids and gases via various methods.…”
Section: Instrumentationmentioning
confidence: 99%
“…Third, the plasma can be operated with multiple arrangements of polarity, rather than the solution only serving as the cathode. (Ray and coworkers have very recently described a device which operates in SCGD and SAGD modes, with magnetic “boosting” for analysis; Hazel et al, 2021). Finally, a diversity of sample introduction modalities can be applied, inclusive of solids, liquids and gases via various methods.…”
Section: Instrumentationmentioning
confidence: 99%
“…[34][35][36] The structure of the SCGD has also been shown to be lamentary in nature when viewed on fast timescales. 37 Since the cathode glow region generally contains the greatest atomic emission yield and little of the background species, increasing the size of the cathode glow region and more effectively capturing the radiation emitted from this region improves the sensitivity and limits of detection of a given analysis. Indeed, Schwartz et al have recently showed that SCGD limits of detection can be improved by 1.4-13.6-times by using spatially-dependent collection of SCGD emission.…”
Section: Introductionmentioning
confidence: 99%